A novel NR5A1 variant in an infant with elevated testosterone from an Australasian cohort of 46, XY patients with disorders of sex development. (12th March 2013) - Wu, Joyce Y.; McGown, Ivan N.; Lin, Lin; Achermann, John C.; Harris, Mark; Cowley, David M.; Aftimos, Salim; Neville, Kristen A.; Choong, Catherine S.; Cotterill, Andrew M.
Summary Background NR5A1 loss‐of‐function mutations are increasingly found to be the cause of 46, XY disorders of sex development (DSD). Objective To determine the presence of NR5A1 mutations in an Australasian cohort of 17 46, XY DSD patients with presumed androgen insensitivity syndrome (AIS) who were negative for androgen receptor gene (AR) mutation. Design Exons 2‐7 of NR5A1 were PCR amplified and sequenced. Gene expression and cellular localization studies were performed on a novel NR5A1 variant c.74A>G (p.Y25C) identified in this study. Results We identified one novel mutation, c.74A>G (p.Y25C) in a patient characterized by penoscrotal hypospadias with bifid scrotum. He had elevated testosterone and gonadotropins in early infancy. Functional analysis of p.Y25C in vitro demonstrated reduced transcriptional activation by SF‐1 and partially impaired nuclear localization in a proportion of transfected human adrenal NCI‐H295R cells. Conclusion This is the first reported case of a DSD patient with a NR5A1 mutation and elevated testosterone levels. Our finding supports evaluation of NR5A1 mutations in 46, XY DSD patients with a range of testosterone levels.